RBSARS: Risk-based structural audit and reporting system using Autodesk BIM360 digital engineering documentation platform - Sanguyo, Christian Paul D. (Animo Repository, 2023)
Structural appraisals play a crucial role in ensuring the overall safety and structural integrity of a building. This Practicum paper focuses on improving Arcadis' existing documentation process for structural appraisals of existing shopping centers in Australia, which currently relies on a time-consuming traditional 'pen and paper' approach. The paper proposes an enhanced workflow that incorporates digital tools like BIM360 throughout the documentation process. This workflow also includes digitizing the existing structural appraisal toolkits used in previous audits by adding Macro to seamlessly capture data extracted from the BIM360 Cloud system and update corresponding risk and defect registers. The results of this Practicum paper provided significant benefits to Arcadis and the field of Structural Engineering, specifically enabling structural engineers to work more efficiently, accurately, and collaboratively with other disciplines and stakeholders with the help of the digital tool. The developed digital process for conducting structural appraisals is scalable, efficient in capturing and analyzing data, flexible for various engineering purposes, replicable for different types of investigations, automated for direct extraction of defect reports, and provides better output for clients in terms of performance. It has the potential to streamline multiple structural appraisals in a short amount of time, making it suitable for building inspections, post-disaster investigations, and other purposes.